Time-cost optimization of building projects - Waheed, Uzair (Project Management Institute, 2015)
Using extensive examples and taking into account all the factors that may come into play, this practical resource illustrates how project managers might find ways to execute their plans in a manner that saves both time and cost, resulting in added profitability for their projects. --